MOTHERHOOD IN PARENTING TABLOID - Yulistiyanti Yulistiyanti (Dinamika Bahasa dan Budaya, 2017)
This article discusses on gender discourse found in parenting articles of on-line parenting tabloid. The articles tell about how to take care children at below five years old. Articles in parenting tabloid inform to young parents about children’s and mother’s health and growth.  The data are taken from caring children articles of Indonesian parenting tabloids. It focuses on articles on children’s growth and health, which traditionally becomes mother’s responsibility. Nowadays, there is change in caring children also used as slogan for some parenting tabloids and magazines that is parenthood. Caring children is not completely handled by mother, but father also should contribute his role in it. The data used are analyzed the contribution of mother or parents in caring the children as addressed subject in the articles. In fact, today supports parenthood as the ideal way caring children. Caring children based on gender give social impact. It creates defensive masculinity on men, and they defend the domination.   The data found still show motherhood in caring children, although the tabloids claim as parenting tabloids. Mentioning mother as the target to do what they suggest dominates the data. Some data present parents as the addressed in the beginning, but in the next paragraphs they address mother as the target of the articles. This tabloid has not left old paradigm in caring children into parenthood yet.Key words: motherhood, parenting tabloid, caring, nurturing